Do Running and Strength Exercises Reduce Daily Muscle Inactivity Time? - Taija Finni; Marja Uusi-Vähälä; Arto J. Pesola; Ritva S. Taipale (AIMS Public Health, 2016)
Understanding how a specific exercise changes daily activity patterns is important when designing physical activity interventions. We examined the effects of strength and interval running exercise sessions on daily activity patterns using recordings of quadriceps and hamstring muscle electromyographic (EMG) activity and inactivity. Five male and five female subjects taking part in a 10-week training programme containing both strength and interval running training sessions were measured for daily muscle EMG activities during three days: on a strength day, an interval running day, and a day without exercise. EMG was measured using textile electrodes embedded into sport shorts that were worn 9.1 ± 1.4 hours/day and results are given as % of recording time. During the total measurement time the muscles were inactive 55 ± 26%, 53 ± 30% and 71 ± 12% during strength training day, interval running day, and day without exercise (n.s.). When compared to the day without exercise, the change in muscle inactivity correlated negatively with change in light muscle activity in strength (r = -0.971,p< 0.001) and interval running days (r = -0.965,p< 0.001). While interval running exercise bout induced a more systematic decrease in muscle inactivity time (from 62 ± 15% to 6 ± 6%,p< 0.001), reductions in muscle inactivity in response to strength exercise were highly individual (range 5–70 pp) despite the same training programme. Strength, but not running exercise bout, increased muscle activity levels occurring above 50% MVC (p< 0.05) when compared to a similar period without exercise. The effect of strength exercise bout on totaldaily recording time increased the EMG amplitudes across the entire intensity spectrum. While strength and interval running exercise are effective in increasing muscle moderate-to-vigorous activity when compared to a similar period without exercise, it comprises only a small part of the day and does not seem to have a systematic effect neither to reduce nor induce compensatory increase in the daily muscle inactivity that is highly heterogeneous between individuals.